1967
DOI: 10.1107/s0365110x67000210
|View full text |Cite
|
Sign up to set email alerts
|

X-ray and neutron diffraction studies of β-sulphanilamide

Abstract: The crystal structure of/~-sulphanilamide has been refined from three-dimensional photographic X-ray data and two-dimensional neutron diffraction data. Positional and anisotropic thermal parameters of the non-hydrogen atoms and positional and isotropic thermal parameters of the hydrogen atoms were refined in the X-ray analysis to give a final R index of 4"9 %. Positional and isotropic thermal parameters of the hydrogen atoms were refined in the neutron study. The final residual factors were R(hOl) = 8-0 %, R(h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
36
0
2

Year Published

1970
1970
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(46 citation statements)
references
References 11 publications
8
36
0
2
Order By: Relevance
“…The mean neutron S-O distance exceeds that for X-rays by 0.009 A, after a correction for thermal motion is applied (Cruickshank, 1956). This difference agrees with those obtained for fl-sulphanilamide (O'Connell & Maslen, 1967) and orthanilic acid (Lure, Maslen & Hall, 1970) and those predicted by O'Connell, Rae & Maslen (1966) from theoretical calculations as the net result of an apparent decrease in the bond length due to the S-O d;z bonding and an apparent increase in the bond length due to the displacement of the centroid of the charge cloud towards the lone pair (Dawson, 1964). The mean discrepancy between the X-ray and neutron results for the bond lengths of the benzene ring is 0.012 + 0.006 A, which agrees favourably with the theoretical calculations for a benzene ring with these substituents (O'Connell, Rae & Maslen, 1966), and a difference Fourier synthesis with Fourier terms…”
Section: Discussionsupporting
confidence: 81%
“…The mean neutron S-O distance exceeds that for X-rays by 0.009 A, after a correction for thermal motion is applied (Cruickshank, 1956). This difference agrees with those obtained for fl-sulphanilamide (O'Connell & Maslen, 1967) and orthanilic acid (Lure, Maslen & Hall, 1970) and those predicted by O'Connell, Rae & Maslen (1966) from theoretical calculations as the net result of an apparent decrease in the bond length due to the S-O d;z bonding and an apparent increase in the bond length due to the displacement of the centroid of the charge cloud towards the lone pair (Dawson, 1964). The mean discrepancy between the X-ray and neutron results for the bond lengths of the benzene ring is 0.012 + 0.006 A, which agrees favourably with the theoretical calculations for a benzene ring with these substituents (O'Connell, Rae & Maslen, 1966), and a difference Fourier synthesis with Fourier terms…”
Section: Discussionsupporting
confidence: 81%
“…In the light of the above observations, crystal structure analysis of the title compound, (I) (R = H), has been undertaken. (O'Connell & Maslen, 1967) and agree with the value of 1.402 (2)A in a-sulfanilamide (O'Connor & Maslen, 1965), having trigonal hybridization. However, this bond length is significantly longer than the C--NH2 distance of 1.316 (7) A, in 1,3,5-trinitrobenzene (Cady & Larson, 1965) which shows sp 3 hybridization of the N atom.…”
Section: Introductionsupporting
confidence: 75%
“…Comment 4-Amino-N-(2-pyrimidinyl)benzenesulfonamide, (I), (R = H) is one of the most important 'sulpha' drugs and is useful in the treatment of bacterial infections and extraluminal urinary-tract infections (Aurthur Osol, 1990); its higher homologue (R = CH3), known as sulphamerazine, has been used in combination with other antibiotics (Aurthur Osol, 1990). Crystal structure studies of sulfonamides have revealed the nature of their intermolecular hydrogen bonding (O'Connell & Maslen, 1967), their interaction with protic solvents (Rambaud, Maury, Pauvert, Audran, Lasserre, Berge & Declercq, 1985) and their binding with specific proteins (Acharya, Kuchela & Kartha, 1982). The crystal structure of sulphadiazine (I) (R = H) has been reported (Ihn, Kim & Koo, 1975) and interesting variations of its solid-state conformation have been found in its silver and zinc complexes (Cook & Turner, 1975;Brown, Cook & Sengier, 1985).…”
Section: Introductionmentioning
confidence: 99%
“…This drug is a homolog of sulfanilamide, but in this case the amino group is no longer aromatic. The crystal structure of sulfanilamide has already been studied in its three forms (O'Connor & Maslen, 1965;O'Connell & Maslen, 1967;All6 aume & Decap, 1965) and it will be interesting to compare its structural parameters with those of 4-homosulfanilamide hydrochloride.…”
Section: Introductionmentioning
confidence: 99%